2018
DOI: 10.1002/ecm.1304
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation determines which feedbacks drive and alter predator–prey eco‐evolutionary cycles

Abstract: Evolution can alter the ecological dynamics of communities, but the effects depend on the magnitudes of standing genetic variation in the evolving species. Using an eco‐coevolutionary predator–prey model, I identify how the magnitudes of prey and predator standing genetic variation determine when ecological, evolutionary, and eco‐evolutionary feedbacks influence system stability and the phase lags in predator–prey cycles. Here, feedbacks are defined by subsystems, i.e., the dynamics of a subset of the componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 92 publications
(267 reference statements)
5
73
0
Order By: Relevance
“…Experimental and theoretical evidence has shown that the amount of genetic variation can affect the link of rapid evolution to population dynamics (Becks et al, 2010;Cortez, 2017;Steiner & Masse, 2013), with increasing additive genetic variation leading to a higher probability of altering the population dynamics. Thus, factors or processes that affect standing genetic variation can have a substantial impact on the evolution-to-ecology link.…”
Section: Reduction In Standing Genetic Variationmentioning
confidence: 99%
“…Experimental and theoretical evidence has shown that the amount of genetic variation can affect the link of rapid evolution to population dynamics (Becks et al, 2010;Cortez, 2017;Steiner & Masse, 2013), with increasing additive genetic variation leading to a higher probability of altering the population dynamics. Thus, factors or processes that affect standing genetic variation can have a substantial impact on the evolution-to-ecology link.…”
Section: Reduction In Standing Genetic Variationmentioning
confidence: 99%
“…By holding the prey trait or predator trait fixed, the coevolutionary model reduces to a model with a single evolving species. Throughout, we only focus on systems at stable equilibrium and do not consider systems exhibiting eco-evolutionary cycles; the cyclic dynamics of the model when one or both species are evolving have been studied previously by the authors (Cortez and Ellner 2010, Cortez 2015, 2018 We also assume increased predator offense comes at the cost of increased mortality (e.g., resistance to newt toxicity in garter snakes comes at the cost of reduced survival due to reduced speed; Brodie and Brodie 1999).…”
Section: Eco-coevolutionary Modelmentioning
confidence: 99%
“…Individual prey with higher defense are assumed to be better defended against all predator phenotypes and individual predators with higher offense are assumed to have higher capture rates for all prey phenotypes; this corresponds to a unidirectional axis of vulnerability (Abrams 2000). Throughout, we only focus on systems at stable equilibrium and do not consider systems exhibiting eco-evolutionary cycles; the cyclic dynamics of the model when one or both species are evolving have been studied previously by the authors (Cortez and Ellner 2010, Cortez 2015, 2018…”
Section: Eco-coevolutionary Modelmentioning
confidence: 99%
“…In general, stability of a whole system is influenced by the effects species’ densities have on the dynamics of population densities (ecological feedbacks), the effects species’ traits have on the dynamics of evolving traits (evolutionary feedbacks), and the effects population densities and evolving traits have on each other’s dynamics (eco-evolutionary feedbacks). Previous theoretical work (7; 15; 16; 17) has explored when these feedbacks have stabilizing versus destabilizing effects, and shown that the strengths of those effects increase or decrease with changes in the relative rates of ecological and evolutionary change. Specifically, stability of the whole system in the slow evolution limit is determined by ecological and eco-evolutionary feedbacks whereas stability of the whole system in the fast evolution limit is determined by evolutionary and eco-evolutionary feedbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Building on prior theoretical work (7; 15; 16), we develop a method using feedbacks defined in terms of the stability of a subsystem, i.e., the interactions and dynamics of a set of variables when all other variables are held fixed (e.g., the ecological subsystem defines the dynamics of all population densities when all population-level traits are held fixed). Our method identifies how the stabilities of complementary pairs of subsystems (e.g., ecological vs. evolutionary subsystems) at the equilibrium of the whole system and the interactions between them (e.g., the effects the evolutionary subsystem has on the ecological subsystem) influence the stability of the whole system.…”
Section: Introductionmentioning
confidence: 99%